A general model of the thermal constraints on the world's most destructive locust, Schistocerca gregaria. Issue 4 (7th April 2021) - Maeno, Koutaro Ould; Piou, Cyril; Kearney, Michael R.; Ould Ely, Sidi; Ould Mohamed, Sid'Ahmed; Jaavar, Mohamed El Hacen; Ould Babah Ebbe, Mohamed Abdallahi
Abstract: All terrestrial ectotherms are constrained to some degree by their thermal environment and the extent to which they can behaviorally buffer variable thermal conditions. New biophysical modeling methods (NicheMapR) allow the calculation of the body temperature of thermoregulating animals anywhere in the world from first principles, but require detailed observational data for parameterization and testing. Here we describe the thermoregulatory biology of marching bands of the desert locust, Schistocerca gregaria, in the Sahara Desert of Mauritania where extreme heat and strong diurnal fluctuations are a major constraint on activity and physiological processes. Using a thermal infrared camera in the field, we showed that gregarious nymphs altered the microhabitats they used, as well as postural thermoregulatory behaviors, to maintain relatively high body temperature (nearly 40°C). Field and laboratory experiments demonstrated that the preferred body temperature accelerated digestive rates. Migratory bands frequently left foraging sites with full guts before consuming all vegetation and moved to another habitat before emptying their foregut. Thus, the repertoire for behavioral thermoregulation in the desert locust strongly facilitates foraging and digestion rates, which may accelerate developmental rates and increase survival. We used our data to successfully parameterize a general biophysical model of thermoregulatory behavior that could capture hourly body temperature and activity at our remote site using globally available environmental forcing data. This modeling approach provides a stronger basis for forecasting thermal constraints on locust outbreaks under current and future climates.